A two-stage anammox process for the advanced treatment of high-strength ammonium wastewater: Microbial community and nitrogen transformation. (10th July 2020) - Fan, Nian-Si; Bai, Yu-Hui; Wu, Jing; Zhang, Quan; Fu, Jin-Jin; Zhou, Wan-Ling; Huang, Bao-Cheng; Jin, Ren-Cun
Abstract: To achieve the efficient treatment of high-strength ammonium wastewaters, a two-stage anammox process was proposed in this study. The nitrogen loading rates (NLR) of two anammox reactors were increased to 60.19 g N L −1 d −1 (R1 ) and 24.32 g N L −1 d −1 (R2 ), through reducing hydraulic retention time (HRT) and increasing ammonium concentration. Afterwards, the reactors were operated in series at variable temperatures (6.15–34.13 °C) for 240 days to treat the synthetic high-ammonium containing wastewater, with the effluent of R1 pumping into R2 as influent. Finally, the advanced treatment of the high-strength ammonium wastewater (490 mg NH4 + -N L −1 and 980 mg TN L −1 ) was successfully achieved, and nitrogen removal efficiency (NRE) maintained at 83.25 ± 9.48%. During the whole operational period (400 days), the richness and diversity of microbial community in two reactors generally increased, and Candidatus Kuenenia was identified as the dominant anammox bacterium. In serial-operation phase, the dominant phylum changed from Planctomycetes to Proteobacteria, and the average relative abundance of Proteobacteria 39.61% in R1 and 48.32% in R2 . Variations in bacterial abundances and distributions were closely related to the substrate concentration and temperature. Correspondingly, the expression levels of most functional genes were reduced by low temperature, and were slightly different in settling, middle and floating sludge. Nitrogen transformation pathway in each phase was also determined based on the gene expression levels, and main pathways in both reactors included anammox and first step of denitrification (NO3 − →NO2 − ). All findings of this study provide new insights into the potential application of the two-stage anammox process to treat high-strength ammonium wastewater under variable temperature conditions. Graphical abstract: Image 1 Highlights: A novel anammox process was proposed to treat high-strength ammonium wastewater. The two-stage anammox process could maintain efficient and stable for a long term. Microbial community composition and distribution changed. Expression levels of functional genes were slightly affected by low temperature. Main nitrogen transformation pathways included anammox and NO3 − .→NO2 − .